An Approach for the Visualization of Temperature Distribution in Tissues According to Changes in Ultrasonic Backscattered Energy. (24th October 2013) - Xia, Jingjing; Li, Qiang; Liu, Hao-Li; Chen, Wen-Shiang; Tsui, Po-Hsiang
Abstract : Previous studies developed ultrasound temperature-imaging methods based on changes in backscattered energy (CBE) to monitor variations in temperature during hyperthermia. In conventional CBE imaging, tracking and compensation of the echo shift due to temperature increase need to be done. Moreover, the CBE image does not enable visualization of the temperature distribution in tissues during nonuniform heating, which limits its clinical application in guidance of tissue ablation treatment. In this study, we investigated a CBE imaging method based on the sliding window technique and the polynomial approximation of the integrated CBE (ICB E pa image) to overcome the difficulties of conventional CBE imaging. We conducted experiments with tissue samples of pork tenderloin ablated by microwave irradiation to validate the feasibility of the proposed method. During ablation, the raw backscattered signals were acquired using an ultrasound scanner for B-mode and ICB E pa imaging. The experimental results showed that the proposed ICB E pa image can visualize the temperature distribution in a tissue with a very good contrast. Moreover, tracking and compensation of the echo shift were not necessary when using the ICB E pa image to visualize the temperature profile. The experimental findings suggested that the ICB E pa image, a new CBE imaging method, has a great potential in CBE-based imaging of hyperthermia and other thermal therapies.